Anthurium Diseases: Identification and Control in Commercial Greenhouse Operations - David J. Norman; Gul Shad Ali (EDIS)
Because of its attractive, long-lasting flowers, Anthurium is popular as both an exotic cut-flower crop and as a flowering potted-plant crop. Growers most often report two bacterial diseases and three fungal diseases in their commercial greenhouse environments. This article provides guidelines to identify and treat diseases that may be encountered during commercial greenhouse production of Anthurium. This 7-page fact sheet was written by David J. Norman and Gul Shad Ali, and published by the UF Department of Plant Pathology, March 2012.